Patterns of empire the British and American empires, 1688 to the present - Go, Julian 1970- (Cambridge University Press, 2011)
Patterns of Empire comprehensively examines the two most powerful empires in modern history: the United States and Britain. Challenging the popular theory that the American empire is unique, Patterns of Empire shows how the policies, practices, forms and historical dynamics of the American empire repeat those of the British, leading up to the present climate of economic decline, treacherous intervention in the Middle East and overextended imperial confidence. A critical exercise in revisionist history and comparative social science, this book also offers a challenging theory of empire that recognizes the agency of non-Western peoples, the impact of global fields and the limits of imperial power